PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Syaakir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
The enhancement of islamic banking as a bank which applies profit sharing system is a benchmark of islamic economic (ekonomi syariah) implementation. In indonesia, islamic banking development witnesses an increase over years yet sequentially. Some factors regarding the steady growth are owing to the crisis hit the world in 2013, besides the lack of cqpital owned by islamic banking in expanding its network. Hence, to tackle these problems, government participation is required in the development of islamic banking along with the need for consolidation of islamic banking as an evaluation in order to face the alteration of economic phenomenon occurence